2010
DOI: 10.1590/s1516-89132010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moisture content and inoculum on the growth and conidia production by Beauveria bassiana on wheat bran

Abstract: The aim of the present work was to study the effect of moisture content and inoculum on the growth and conidia production by Beauveria bassiana on wheat bran (WB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 20 publications
1
12
0
14
Order By: Relevance
“…Similar response of moisture content on inulinase production by Pichia guilliermondii in SSF has also been reported (18). Nuñez-Gaona et al (19) also reported that only a certain level of moisture is enough to accelerate nutrient absorption, normal metabolic function and fungal conidial production. Requirement of moisture content can vary from species to species.…”
Section: Effect Of Independent Variables and Their Interactions On Insupporting
confidence: 73%
See 1 more Smart Citation
“…Similar response of moisture content on inulinase production by Pichia guilliermondii in SSF has also been reported (18). Nuñez-Gaona et al (19) also reported that only a certain level of moisture is enough to accelerate nutrient absorption, normal metabolic function and fungal conidial production. Requirement of moisture content can vary from species to species.…”
Section: Effect Of Independent Variables and Their Interactions On Insupporting
confidence: 73%
“…Requirement of moisture content can vary from species to species. Generally, minimum of 20 % of moisture level is essential for fungal growth, while very high moisture content may retard conidial induction (19). The increase in pH up to 7.0 has also shown a significant influence on inulinase production.…”
Section: Effect Of Independent Variables and Their Interactions On Inmentioning
confidence: 99%
“…Commonly an inoculum concentration of 1 × 10 7 spores g -1 is recommended (Arzumanov et al 2005;Nuñez-Gaona et al 2010). In the present study, the statistical analysis suggested that it was possible to choose an inoculum level between 10 6 and 10 7 spores g -1 that resulted in the same spore production.…”
Section: Optimization For Spore Production Via Bbmmentioning
confidence: 58%
“…A marked decrease in spore production was pointed out when the inoculum level was 1 × 10 9 spores g -1 . Inoculum levels have also been evaluated for other fungal biocontrol agents such as Beauveria bassiana by Nuñez-Gaona et al (2010), who tested concentrations of 1 × 10 6 , 7 × 10 6 , and 5 × 10 7 spores g -1 through SSF of wheat bran. The three levels of inoculum evaluated resulted in high spore production (1.08 × 10 10 to 1.53 × 10 10 spores g -1 ).…”
Section: Optimization For Spore Production Via Bbmmentioning
confidence: 99%
See 1 more Smart Citation